1998
DOI: 10.1038/1289
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for hereditary thyroid dysgenesis and cleft palate

Abstract: Alteration of thyroid gland morphogenesis (thyroid dysgenesis) is a frequent human malformation. Among the one in three to four thousand newborns in which congenital hypothyroidism is detected, 80% have either an ectopic, small and sublingual thyroid, or have no thyroid tissue. Most of these cases appear sporadically, although a few cases of recurring familial thyroid dysgenesis have been described. The lack of evidence for hereditary thyroid dysgenesis may be due to the severity of the hypothyroid phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
209
1
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(221 citation statements)
references
References 19 publications
4
209
1
7
Order By: Relevance
“…A homeodomain transcription factor, T/ebp (also called Ttf1, Titf1, or Nkx2.1) (Guazzi et al, 1990;Mizuno et al, 1991), is one of the transcription factors essential for regulating the expression of genes involved in thyroid hormone synthesis as well as thyroid organogenesis (Kimura et al, 1996;De Felice et al, 1998;Mansouri et al, 1998;Damante et al, 2001;Di Lauro and De Felice, 2001;De Felice and Di Lauro, 2004). Mice carrying a null mutation for T/ebp gene die at birth due to profoundly hypoplastic lungs, a defective hypothalamus, and absence of the thyroid and pituitary glands (Kimura et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A homeodomain transcription factor, T/ebp (also called Ttf1, Titf1, or Nkx2.1) (Guazzi et al, 1990;Mizuno et al, 1991), is one of the transcription factors essential for regulating the expression of genes involved in thyroid hormone synthesis as well as thyroid organogenesis (Kimura et al, 1996;De Felice et al, 1998;Mansouri et al, 1998;Damante et al, 2001;Di Lauro and De Felice, 2001;De Felice and Di Lauro, 2004). Mice carrying a null mutation for T/ebp gene die at birth due to profoundly hypoplastic lungs, a defective hypothalamus, and absence of the thyroid and pituitary glands (Kimura et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…TTF-2 mRNA is expressed in the endoderm lining the foregut, in the developing thyroid, and in the ectoderm that gives rise to the anterior pituitary (Zannini et al, 1997;Parlato et al, 2001). Gene targeting experiments have demonstrated that titf2/foxe1 null mice exhibit cleft palate and either a sublingual or completely absent thyroid gland (De Felice et al, 1998). In humans, mutations of the gene encoding for TTF-2 result in the Bamforth syndrome, characterized by thyroid agenesis, cleft palate, spiky hair, and choanal atresia (Clifton-Bligh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient of Nkx2-1, Pax8, Foxe1 or Hhex are well-studied models of athyreosis, i.e. the primordium is correctly specified but eventually regresses leading to a lack of thyroid tissue in late stages of development (Kimura et al, 1996;Mansouri et al, 1998;De Felice et al, 1998;Martinez Barbera et al, 2000). These transcription factors are thus not individually required for thyroid specification or early bud formation.…”
Section: Survival and Growth Of Thyroid Progenitors Depend On A Thyromentioning
confidence: 99%
“…Foxe1 deficient mice are born at an expected ratio but die in the early postnatal period, probably due to the severe cleft palate (De Felice et al, 1998). No orthotopic thyroid is present and hormone analysis reveals severe CH.…”
Section: Foxe1mentioning
confidence: 99%
See 1 more Smart Citation